Organ donation after euthanasia in a patient living with dementia: a landmark case report - van Dijk, Nathalie; Vliegen, Fabiënne; Ham, Angelique; de Jongh, Wim; Berkhout, Freek Jan; Blankevoort, Jeroen; ten Hoopen, Rankie; Bollen, Jan; van Mook, Walther (Frontiers in Dementia, 2023)
This article provides insights into how a patient living with dementia last wish for organ donation after euthanasia can be granted within the legal and ethical boundaries, scaffolded around a unique illustrative practice case of a patient with primary progressive aphasia, subtype logopenic variant, as part of frontotemporal dementia.